CONCENTRATIONS OF IgG SUBCLASSES IN ALLOGENEIC BONE MARROW RECIPIENTS - A. V. Klimovich (SPb RAACI, 2014)
A sufficient increase of infectious complications rate during early posttransplant period in allogeneic bone marrow (allo-BM) recipients has been traditionally explained by the prominent drop of serum IgG levels in the patients. That was the main reason for therapeutic application of intravenous human immunoglobulins in allo-BM-recipients. In present study, multiple repeated measurements of different IgG subclasses were performed in blood serum of thirty-six patients at early terms after allogenic bone marrow transplantation period, along with analysis of individual clinical data. The study revealed several factors that show significant associations with IgG levels posttransplant. Moderate decrease in concentrations of IgG subclasses was registered after conditioning treatment carried out before the transplantation. Significantly decreased concentrations of IgG subclasses have been revealed during bleedings, diarrhea and glucocorticosteroid therapy. In general, however, no regular prolonged deficiency for total IgG subclasses was found in allogeneic bone marrow recipients during early posttransplant period.